M2 tumor-associated macrophages produce interleukin-17 to suppress oxaliplatin-induced apoptosis in hepatocellular carcinoma - Guo, Bin (Oncotarget, 2017)
M2 macrophages are a major component of the tumor microenvironment and are important promoters of tumor occurrence and progression. In this study, we detected large numbers of M2 macrophages in hepatocellular carcinoma tissues using immunohistochemistry and immunofluorescence. Moreover, upon oxaliplatin treatment, the M2 macrophages overexpressed interleukin-17, an important inflammatory cytokine, and thus inhibited oxaliplatin-induced apoptosis. By knocking down the interleukin-17 receptor and lysosome-associated membrane protein 2A (a key protein in chaperone-mediated autophagy) in hepatocellular carcinoma cells, we found that interleukin-17 stimulated chaperone-mediated autophagy, which further suppressed apoptosis upon oxaliplatin treatment. Chaperone-mediated autophagy induced tolerance to oxaliplatin treatment by reducing cyclin D1 expression; thus, cyclin D1 overexpression stimulated oxaliplatin-induced apoptosis. In addition, cyclin D1 expression was inhibited by interleukin-17, but increased when the interleukin-17 receptor was knocked down. Thus M2 macrophages in the hepatocellular carcinoma microenvironment generate large amounts of interleukin-17, which suppress oxaliplatin-induced tumor cell apoptosis by activating chaperone-mediated autophagy and in turn reducing cyclin D1 expression. These findings may facilitate the development of novel therapeutic strategies for chemorefractory liver cancer.